Patterns of Medical Pluralism in Health-Seeking Behavior among Communities in Barru Regency, South Sulawesi, Indonesia - Nurul Auliah Nasrullah; Nurgah Tandirerung; Ivan Prayogi; Ibrahim Arifin (CV. Yazri Aksara Nusantara, 2026)
This study examines how medical pluralism shapes health-seeking behavior among communities in Barru Regency, South Sulawesi, by analyzing the roles of cultural beliefs, clinical experience, and economic as well as accessibility factors in treatment decision-making. Employing a qualitative descriptive–exploratory design, data were collected through in-depth interviews, non-participant observation, and document review involving community members, traditional healers, and formal health practitioners. Thematic analysis identified three main findings: culturally grounded beliefs that legitimize traditional medicine as a holistic and spiritually meaningful initial reference; clinically based trust that positions biomedical services as the primary source of diagnostic certainty and the management of serious illness; and economic and accessibility considerations that influence the sequence and intensity of health service utilization. These findings indicate that health-seeking behavior in Barru Regency is characterized by a sequential and complementary pattern of medical pluralism rather than a dichotomous opposition between traditional and modern medicine. Theoretically, this study contributes to the literature on health-seeking behavior by conceptualizing medical pluralism as a contextual social strategy, while practically highlighting the importance of culturally sensitive and integrative health service approaches. Penelitian ini bertujuan menganalisis bagaimana pluralisme medis membentuk perilaku pencarian pengobatan masyarakat di Kabupaten Barru, Sulawesi Selatan, dengan menelaah peran kepercayaan budaya, pengalaman klinis, serta faktor ekonomi dan aksesibilitas dalam pengambilan keputusan berobat. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif-eksploratif melalui wawancara mendalam, observasi nonpartisipatif, dan telaah dokumen yang melibatkan masyarakat, penyembuh tradisional, dan tenaga kesehatan formal. Analisis tematik menunjukkan tiga temuan utama, yaitu kepercayaan berbasis budaya yang melegitimasi pengobatan tradisional sebagai rujukan awal yang holistik dan bermakna spiritual, kepercayaan berbasis pengalaman klinis yang menempatkan layanan biomedis sebagai sumber utama kepastian diagnosis dan penanganan penyakit serius, serta faktor ekonomi dan aksesibilitas yang memengaruhi urutan serta intensitas pemanfaatan layanan kesehatan. Temuan ini menunjukkan bahwa perilaku pencarian pengobatan masyarakat Barru dicirikan oleh pola pluralisme medis yang berurutan dan saling melengkapi, bukan pertentangan antara sistem tradisional dan modern. Secara teoretis, penelitian ini memperkaya kajian health-seeking behavior dengan memosisikan pluralisme medis sebagai strategi sosial yang kontekstual, sementara secara praktis menegaskan pentingnya pendekatan layanan kesehatan yang integratif dan sensitif budaya.